Efektivitas Layanan Bimbingan Belajar dalam Membantu Kegiatan Pembelajaran Daring dari Sekolah - Sugianto, Rian (Universitas Sebelas Maret, 2020)
The implementation of learning activities in schools has undergone a very big change with the covid-19 pandemic in Indonesia, learning activities that were initially carried out face-to-face in schools were replaced with online learning or commonly known as online learning. This change certainly has a serious impact on the systems and techniques of implementing educational activities in Indonesia, especially in school learning activities. The pros and cons of course become a natural thing when there is a change in policy. Online learning is not only technically problematic, but the essence or purpose of learning has not really been tested for its effectiveness in the online learning system. This study uses descriptive qualitative research that describes tutoring services in reducing students' learning difficulties during the COVID-19 pandemic. The results showed that the barriers to online learning were parents of ignorant students, internet access, difficulty understanding the material, feeling lazy and having difficulty concentrating. The solutions are: making online learning media systems, communicating with parents, making learning summaries, giving assignments that encourage students to be active.